Routledge handbook of comparative constitutional change (Routledge, 2020)
The Routledge Handbook of Comparative Constitutional Change provides a comprehensive reference tool for all those working in the field and a thorough landscape of all theoretical and practical aspects of the topic. Coherence from this aspect does not suggest a common view, as the chapters address different topics, but reinforces the establishment of Comparative Constitutional Change as a distinct field. The book brings together the most respected scholars working in the field, and presents a genuine contribution to comparative constitutional studies, comparative public law, political science and constitutional history"--